ASSISTANCE IN RELIGIOUS DEVELOPMENT OF THE SEBYAR MUSLIM COMMUNITY, SORONG REGENCY - Khatipah Khatipah; Aprilia Nurhayati; Irma Shintya; Miftahulfadlik Dabamona (KARYA ABDI, 2022)
The Muslim community of the Sebyar Bintuni Tribe of Sorong Regency is one of the indigenous Papuan tribes that have long been residents of Sorong Regency with lack knowledge of Islamic teachings. This community empowerment program is desinged to carry out the planned program in order to solve various problems that have been experienced by the tribe. Participatory Action Research (PAR) is employed in this community service program through the development of the taklim assembly "Andi Agora", the Muslim children of the sebyar tribe have gained insight and understanding related to the fiqh of Worship and practiced it in their daily lives. in addition, through the development of kindergarten / landfill for muslim children, the muslims of seyyed tribe are equipped with basic islamic insights, such as recitation, ablution, prayer, daily prayers, and short surahs.